Determination of the level of tactical readiness of qualified runners at 800 m - Rybalchenko, T.; Nasonkina, O.; Marchenkov, M. (Slobozhanskyi herald of science and sport, 2018)
Purpose: determine the change in the level of tactical preparedness and tactics of competitive activity of qualified runners at 800 m.